Association of cardiovascular disease risk factors with coronary artery calcium volume versus density. Issue 2 (16th August 2017) - Thomas, Isac C; Shiau, Brandon; Denenberg, Julie O; McClelland, Robyn L; Greenland, Philip; de Boer, Ian H; Kestenbaum, Bryan R; Lin, Gen-Min; Daniels, Michael; Forbang, Nketi I; Rifkin, Dena E; Hughes-Austin, Jan; et al.
Abstract : Objectives: Recently, the density score of coronary artery calcium (CAC) has been shown to be associated with a lower risk of cardiovascular disease (CVD) events at any level of CAC volume. Whether risk factors for CAC volume and CAC density are similar or distinct is unknown. We sought to evaluate the associations of CVD risk factors with CAC volume and CAC density scores. Methods: Baseline measurements from 6814 participants free of clinical CVD were collected for the Multi-Ethnic Study of Atherosclerosis. Participants with detectable CAC (n=3398) were evaluated for this study. Multivariable linear regression models were used to evaluate independent associations of CVD risk factors with CAC volume and CAC density scores. Results: Whereas most CVD risk factors were associated with higher CAC volume scores, many risk factors were associated with lower CAC density scores. For example, diabetes was associated with a higher natural logarithm ( ln ) transformed CAC volume score (standardised β=0.44 (95% CI 0.31 to 0.58) ln-units) but a lower CAC density score (β=−0.07 (−0.12 to −0.02) density units). Chinese, African-American and Hispanic race/ethnicity were each associated with lower ln CAC volume scores (β=−0.62 (−0.83to −0.41), −0.52 (−0.64 to −0.39) and −0.40 (−0.55 to −0.26) ln-units, respectively) and higher CAC density scores (β= 0.41 (0.34 to 0.47), 0.18 (0.12 to 0.23) and 0.21 (0.15 to 0.26) density units, respectively) relative to non-Hispanic White. Conclusions: In a cohort free of clinical CVD, CVD risk factors are differentially associated with CAC volume and density scores, with many CVD risk factors inversely associated with the CAC density score after controlling for the CAC volume score. These findings suggest complex associations between CVD risk factors and these components of CAC.